2019
DOI: 10.1016/j.rser.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of ICT on household behavioural energy efficiency to mitigate global warming

Abstract: Growing self-generation and storage are expected to cause significant changes in residential electricity utilization patterns. Commonly applied volumetric network tariffs may induce imbalance between different groups of households and their respective contribution to recovering the operating costs of the grid. Understanding consumer behaviour and appliance usage together with socio-economic factors can help regulatory authorities to adapt network tariffs to new circumstances in a fair way. We assess the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(96 citation statements)
references
References 43 publications
(8 reference statements)
2
72
0
1
Order By: Relevance
“…On the one hand, early studies, including those of Walker (1986) and Chen (1994), generally concluded that ICT and energy were substitutes for each other and that ICT would reduce energy use. Empirically, some studies find that the application of ICT can promote energy efficiency and productivity and thereby contribute to reducing energy intensity (Røpke and Christensen, 2012;Corbett, 2013;Cai et al, 2013;Wang and Han, 2016;Bastida et al, 2019;Avom et al, 2020). For example, Røpke and Christensen (2012) pointed out that ICT has great potential for reducing energy consumption but that this depends on economic and political conditions.…”
Section: Technologies and Energy Intensitymentioning
confidence: 99%
“…On the one hand, early studies, including those of Walker (1986) and Chen (1994), generally concluded that ICT and energy were substitutes for each other and that ICT would reduce energy use. Empirically, some studies find that the application of ICT can promote energy efficiency and productivity and thereby contribute to reducing energy intensity (Røpke and Christensen, 2012;Corbett, 2013;Cai et al, 2013;Wang and Han, 2016;Bastida et al, 2019;Avom et al, 2020). For example, Røpke and Christensen (2012) pointed out that ICT has great potential for reducing energy consumption but that this depends on economic and political conditions.…”
Section: Technologies and Energy Intensitymentioning
confidence: 99%
“…For this reason, the authors put the focus on how to get users' attention and educate them to increase customer awareness and participation in demand management. Accordingly, Bastida et al [139] analyses the role of the consumers' behaviour with respect to the potential of ICT-based interventions to decrease electricity usage in households. In this work, they addressed motivating, reinforcing and enabling factors to encourage lasting behaviours and analysed their impact on the efficacy of ICT approaches to mitigate CO 2 emissions.…”
Section: Discussionmentioning
confidence: 99%
“…The operation of flexible loads is executed at a fixed a priori cost. If a flexible load diverges at a given hour from the value of the original load, then that change is penalized by a cost (8). Therefore, the load deviation y REG is penalized either if it is positive or negative.…”
Section: The New Objective Functionmentioning
confidence: 99%